Report of the National Forest Commission - Planning Commission (Planning Commission, 2006)
Pursuant upon the recommendation made by the Indian Board of Wildlife in its 21st meeting held on 21 January 2002 under the chairmanship of Honourable Prime Minister of India, Government of India resolved to constitute a National Forest Commission to review the working of the forest and wildlife sector. The resolution recalled that the livelihood issue of around seven crore tribal and more than 20 crore non-tribal rural population is linked with the forest. The necessity of meeting the demand for wood for commercial and industrial purposes through agroforestry and plantations, and the desirability of evolving appropriate strategy and knowledge base for in situ conservation and ex situ propagation of medicinal plants in view of their increasing demand, were further recognized.
Government of India Ministry of Environment and Forests
Government of India Ministry of Environment and Forests